New chemodosimetric probe for the specific detection of Hg2+ in physiological condition and its utilisation for cell imaging studies - Saha, Sukdeb; Agarwalla, Hridesh; Gupta, Hariom; Baidya, Mithu; Suresh, E.; Ghosh, Sudip K.; Das, Amitava (Dalton Transactions, 2013)
A dithiane derivative of BODIPY is synthesized. This new reagent could be used for the specific and instantaneous detection of Hg2+ in physiological condition. This dithiane reagent reacts specifically with Hg2+ to regenerate the parent BODIPY-aldehyde with consequential change in visually detectable optical responses and this provides the possibility of using this reagent as a colorimetric probe or as a fluorescent biomarker/imaging reagent. Further, non-covalent interactions could be utilized for formation of an inclusion complex with biologically benign beta-cyclodextrin for enhancing its solubility in aqueous environment and this included adduct could be used as a fluorescent marker and imaging reagent for Hg2+. Uptake of Hg2+ ions in live HeLa cells, exposed to a solution having Hg2+ ion concentration as low as 2 ppb, could also be detected by confocal laser microscopic studies.